Integration of Geoelectric and Geochemical Data in the Evaluation of Natural Attenuation in a Diesel Contaminated Site in São Manuel (brazil) - Moreira, César A. [UNESP]; Portes Innocenti Helene, L. [UNESP]; Côrtes, A. R.P. [UNESP] (Universidad Nacional Autonoma de Mexico, 2017)
Geophysics is a very relevant investigation tool in conjunction with chemical analysis, during the diagnosis and monitoring of contamination in the geological environment. This paper presents the results of DCdefine resistivity and Induced Polarization geophysical methods in an area contaminated by diesel due to a railway accident that occurred in 1999 in which no remediation systems were implemented. The processes of natural attenuation prevailing in the area resulted in gradual reduction of the levels of hydrocarbons in groundwater, as demonstrated by a historic series of analyses. The dissolution and neoformation mineral are products of this process that in the availability of elements such as Fe and Mn in tropical soils, often result in the crystallization of sulphide. 2D profiles and 3D geophysical models reveal a central zone of high resistivity and high chargeability in an area with remnants of contamination quantified in 2008, associated to residual hydrocarbons. Besides, the high chargeability data provides an overview of the mineralization of the hydrocarbon as a result from its degradation. The data indicates the possibility of using these methods as an auxiliary tool in systems for remediation of contamination by hydrocarbons, by the possibility of investigations into dry soil and groundwater, and in monitoring metal mineralization, products related to the degradation of hydrocarbons in the geological environment.
Keywords: atenuación natural; cargabilidad; hidrocarburos; resistividad eléctrica